The “father's day” includes transexuals fathers: Dissident masculinities and LGBTTQIA+ artistic practices (Revista Apotheke, 2021)
In 2020, close to the date on which “father's day” is celebrated culturally in Brazil, a national company, popular in the sale of cosmetics, invited 14 men to join a campaign that valued the fathers present, including, Thammy Miranda (1982--), a transsexual man. The initiative generated controversy and division of opinions, exposing controversial ideas not only about "father's day", but also about non-hegemonic masculinities. Hegemonic Masculinity (CONNELL, 1990; 2016) is configured in a conception that describes the “real man” as the one who is indispensable crossed by cisgeneity, heterosexuality, whiteness, the upper-middle class, consumerism, Christianity and for other socially valued identity markers. In this article, we intend to highlight the potential of LGBTTQIA + artistic-academic practices in expanding the meanings given to masculinities. To do this, we first look specifically at some of the reactions related to the campaign in question, and approach them to specific concepts of Masculinity and Gender Studies from a constructivist approach. Subsequently, based on the Research in Art methodology (REY, 1996), we shared the creative process of the authors, gay professors-researchers-artists, in two artistic productions titled 2018 d.C(2020) and Super pai (2020). We consider the artistic treatment and intention given to these productions, they problematize and denounce violent aspects of fatherhood carried out by hegemonic masculinities, and they complain about the expansion of points of view and references from which masculinities are visually represented in school spaces.
Keywords: education; gender; image; transexuality; creative process